Antibacterial and antifungal activities of the endemic species Glaucium vitellinum Boiss. and Buhse - Mina Mehrara; Mehri Halakoo; Mojdeh Hakemi-Vala; Seyyde Jamal Hashemi; Jinous Asgarpanah (Mashhad University of Medical Sciences, 2014)
Objectives: Belonging to Papaveraceae family, Glaucium vitellinum is one of the Persian endemic plants which has not been investigated biologically. The present paper focused on the assessment of the antibacterial and antifungal activities of the total methanol extract and alkaloid sub-fraction of the flowering aerial parts of G. vitellinum. Materials and Methods: The antibacterial and antifungal activities were investigated using cup plate method and disc diffusion assay, respectively. The MIC values of the active samples were determined using micro plate dilution method. Results: The crude extract and alkaloid sub-fraction of G. vitellinum had significant inhibition activity on the growth of S. aureus and S. typhi. From antifungal assay, it is concluded that only the yeast C. albicans, showed a high sensitivity to the extract and especially to the related alkaloid sub-fraction. Conclusions: Regarding the results, G. vitellinum could be employed as a natural antibacterial and antifungal agent against S. aureus, S. typhi, and C. albicans, respectively. Moreover, based on the results of this study, further in vivo and ex vivo confirmatory tests for total methanol extract and alkaloid sub-fraction are recommended.